(untitled) (Bangladesh Journal of Botany, 2021)
To assess the impact of rhizome rot disease management on growth and yield of ginger a study was carried out. Rhizome treatment with copper hydroxide resulted 86% ginger germination followed by Trichoderma viride which was 81% over local check. The results further revealed that rhizome treatment by copper hydroxide and its soil drenching effectively controlled rhizome rot disease (67%) with reduced disease incidence (4.6%) followed by Trichoderma viride which controlled the disease by 53.5% and reduced the disease incidence to 6.8% over local check. Extension and technology gap was recorded 2.5 and 3.8 t/ha. Raised bed planting, use of Trichoderma viride, disease free seed and rhizome treatment were adopted by 53.3, 26.6, 29.3 and 24% respondents.